Polymicrobial biofilm formation by Candida albicans, Actinomyces naeslundii, and Streptococcus mutans is Candida albicans strain and medium dependent - Arzmi, Mohd Hafiz; Alnuaimi, Ali D.; Dashper, Stuart; Cirillo, Nicola; Reynolds, Eric; McCullough, Michael (Oxford University Press, 2016)
Oral biofilms comprise of extracellular polysaccharides and polymicrobial microorgan- isms. The objective of this study was to determine the effect of polymicrobial interac- tions of Candida albicans, Actinomyces naeslundii, and Streptococcus mutans on biofilm formation with the hypotheses that biofilm biomass and metabolic activity are both C. albicans strain and growth medium dependent. To study monospecific biofilms, C. al- bicans, A. naeslundii, and S. mutans were inoculated into artificial saliva medium (ASM) and RPMI-1640 in separate vials, whereas to study polymicrobial biofilm formation, the inoculum containing microorganisms was prepared in the same vial prior inoculation into a 96-well plate followed by 72 hours incubation. Finally, biofilm biomass and metabolic activity were measured using crystal violet and XTT assays, respectively. Our results showed variability of monospecies and polymicrobial biofilm biomass between C. al- bicans strains and growth medium. Based on cut-offs, out of 32, seven RPMI-grown biofilms had high biofilm biomass (HBB), whereas, in ASM-grown biofilms, 14 out of 32 were HBB. Of the 32 biofilms grown in RPMI-1640, 21 were high metabolic activity (HMA), whereas in ASM, there was no biofilm had HMA. Significant differences were observed between ASM and RPMI-grown biofilms with respect to metabolic activity (P < .01). In conclusion, biofilm biomass and metabolic activity were both C. albicans strain and growth medium dependent.